Jejunal atresia associated with jejunal diverticulosis - Hamdi H. Almaramhy (Elsevier, 2018)
Jejunoilial atresia is a frequent cause of bowel obstruction in neonates, with prevalence around 0.7 per 10000 livebirths. It is believed to be related to an intrauterine vascular accident that commonly presents as isolated pathology. Although, other associated anomalies have been reported on rare occasions, the association between the atresia and jejunal diverticulosis in newborn has never been described in literature. Furthermore, jenunal diverticulosis is rare below 40 and never been reported in children. Here in, we share the first reported case of this association and the first case of jejunal diverticulosis in this age category, the challenge in its management and provide review on literature. Keywords: Jejunum, Atresia, Diverticulosis, Neonate, Intestinal obstruction